2018
DOI: 10.1016/j.chembiol.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A Potent and Selective PARP11 Inhibitor Suggests Coupling between Cellular Localization and Catalytic Activity

Abstract: Highlights d Structure-guided design of PARP inhibitors d Identification of a potent and selective PARP11 inhibitor (ITK7) d ITK7 inhibits PARP11 auto-MARylation in cells d ITK7 causes PARP11 to dissociate from the nuclear envelope

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 33 publications
0
62
0
Order By: Relevance
“…The high complexity of ADP-ribosyl associated pathways makes the involved proteins notoriously hard to study (Bonfiglio et al, 2020;Lüscher et al, 2018). While potent and specific inhibitors against many of the ADP-ribosyl transferases fundamentally helped to broaden our understanding of these enzymes (Durkacz et al, 1980;Huang et al, 2009;Kirby et al, 2018;Venkannagari et al, 2016;Wang et al, 2018), such inhibitors against ADP-ribosyl readers and erasers are still scarcely available or in early stages of development (Harrision et al, 2020;James et al, 2016;Liu et al, 2020;Palazzo and Ahel, 2018;Schuller et al, 2017). It was suggested that a possible bottleneck for the discovery of inhibitors is due to the lack of accessible high-throughput technologies (Schuller et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The high complexity of ADP-ribosyl associated pathways makes the involved proteins notoriously hard to study (Bonfiglio et al, 2020;Lüscher et al, 2018). While potent and specific inhibitors against many of the ADP-ribosyl transferases fundamentally helped to broaden our understanding of these enzymes (Durkacz et al, 1980;Huang et al, 2009;Kirby et al, 2018;Venkannagari et al, 2016;Wang et al, 2018), such inhibitors against ADP-ribosyl readers and erasers are still scarcely available or in early stages of development (Harrision et al, 2020;James et al, 2016;Liu et al, 2020;Palazzo and Ahel, 2018;Schuller et al, 2017). It was suggested that a possible bottleneck for the discovery of inhibitors is due to the lack of accessible high-throughput technologies (Schuller et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical success of PARP inhibitors in BRCA1/2-mutated breast and ovarian cancers has ignited a push for more widespread use of these compounds in cancers with a molecular signature of defective HR, irrespec-ADP-ribose mechanisms and disease 7 tive of which HR gene is mutated and in which tissue the tumour originated (Pilie et al, 2019). Similarly, novel inhibitors that selectively target different PARPs, including PARP3, PARP5a/5b, PARP7, PARP10, PARP11 and PARP14 are under investigation for the targeted treatment of cancers with alterations in particular pathways (Ishida et al, 2006;Lindgren et al, 2013;Iwata et al, 2016;Wang, Y. Q. et al, 2016b;Ferri et al, 2017;Yoneyama-Hirozane et al, 2017;Kirby et al, 2018;Moustakim et al, 2018;Murthy et al, 2018).…”
Section: Parp1 and Cell Deathmentioning
confidence: 99%
“…1 Ribon Therapeutics Inc., Cambridge, MA, USA 2 Evotec SE, Hamburg, Germany inhibitors, and of those published, potencies and intra-PARP family selectivity are modest. [3][4][5][6][7][8][9][10] Approved drugs that target PARP1 and PARP2 (niraparib and talazoparib) or PARP1, PARP2, and PARP3 (olaparib and rucaparib) are now in use for the treatment of a variety of cancers, and potent and selective inhibitors of PARP5a and PARP5b (tankyrases 1 and 2) have been reported to have antiproliferative activity in cancer cell lines and in vivo models. 11 MonoPARPs have been reported to have important roles in immunology, inflammation, and cancer; [12][13][14] however, these studies have relied almost exclusively on genetic perturbation techniques that often do not distinguish loss of catalytic activity from loss of the entire protein.…”
Section: Research-article2019mentioning
confidence: 99%